تقييم فعالية التحقيق المحاسبي في تقويم المداخيل تحت إطار الرقابة الجبائية دراسة حالة الجزائر خلال فترة (2010-2018) - دوداح, رضوان; بن عربية, شيراز (جامعة الوادي - University of Eloued, 2022)
سنحاول من خلال هاته الورقة البحثية إبراز فعالية التحقيق المحاسبي على مداخيل الرقابة الجبائية، باعتبار التحقيق المحاسبي أداة من أدوات الرقابة الجبائية للتحقق من مجمل التصريحات الجبائية ومطابقتها مع المعطيات المادية لاكتشاف الأخطاء والتلاعبات سواء عن قصد أو بحسن نية، والتي تؤدي إلى تفاقم ظاهرة الغش والتهرب الضريبي من خلال دراسة إحصائية للمداخيل خلال الفترة 2010-2018 حيث تجلى في نهاية البحث أن العلاقة طردية و ذات فعالية في التحصيل حيث كلما زاد التحقيق في التصريحات زادت المداخيل المتأتية عنها We will try through this research paper to highlight the effectiveness of the accounting investigation on incomes, as an accounting investigation as an integral control tools to verify the total and conformity with material data to detect mistakes and ties, which are intended or in good faith, which exacerbates the phenomenon of fraud and tax evasion Through a statistical study of income during the period 2010-2018, where he was accelerated at the end of the research that the Relationship is prospective and effective in achievement where the greater the investigation into the statements increased income derived from them
Evaluation the effectiveness of the accounting investigation into income, the framework of tax control, the case study of Algeria during the period (2010-2018)
مقال
Keywords: التحقيق المحاسبي ; الرقابة الجبائية ; التصريحات الجبائية ; ظاهرة الغش والتهرب الضريبي; accounting investigation ; tax contro ; tax declarations ; The phenomenon of fraud and tax evasion